2010
DOI: 10.1007/s10499-010-9353-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fatty acid composition of egg capsules from broodstock spotted babylon, Babylonia areolata, fed a local trash fish and formulated diet under hatchery conditions

Abstract: This study is the first attempt to condition broodstock Babylonia areolata using formulated diets under hatchery conditions. Samples of spotted babylon egg capsules from broodstock fed either a formulated diet or a local trash fish, carangid fish (Seleroides leptolepis) for 120 days were analyzed for proximate composition and fatty acid composition. The formulated diet contained significantly higher levels of arachidonic acid (20:4n -6; ARA), eicosapentaenoic acid (20:5n -3; EPA) and docosahexaenoic acid (22:6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Survival metrics: Our research on the B. areolata's survival adaptability across different diets revealed consistent survival rates regardless of dietary variations (P>0.05), as detailed in Table 8. These results align with Chaitanawisuti et al (2011), who also found steady survival rates for snails in varied environments, such as canvas and earthen ponds.…”
Section: Experiments 2: An Analytical Dive Into the Growth Performanc...supporting
confidence: 90%
See 3 more Smart Citations
“…Survival metrics: Our research on the B. areolata's survival adaptability across different diets revealed consistent survival rates regardless of dietary variations (P>0.05), as detailed in Table 8. These results align with Chaitanawisuti et al (2011), who also found steady survival rates for snails in varied environments, such as canvas and earthen ponds.…”
Section: Experiments 2: An Analytical Dive Into the Growth Performanc...supporting
confidence: 90%
“…Cross-comparison with previous research: The weight augmentation of the T1 cohort was congruent with the findings of Chaitanawisuti et al (2011), who reported analogous weight gain trajectories in juvenile snails, both in canvas and earthen ponds. Furthermore, Dobson et al (2020) showcased a comparable weight progression in snails nurtured on trash fish, observing a weight transition from 0.90 ± 0.38 g to 4.93 ± 1.44 g over a 92-day period.…”
Section: Experiments 2: An Analytical Dive Into the Growth Performanc...supporting
confidence: 87%
See 2 more Smart Citations